The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1371/journal.ppat.1011491
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage infectivity potentiator protein, a peptidyl prolyl cis-trans isomerase, essential for Coxiella burnetii growth and pathogenesis

Aleksandra W. Debowski,
Nicole M. Bzdyl,
David R. Thomas
et al.

Abstract: Coxiella burnetii is a Gram-negative intracellular pathogen that causes the debilitating disease Q fever, which affects both animals and humans. The only available human vaccine, Q-Vax, is effective but has a high risk of severe adverse reactions, limiting its use as a countermeasure to contain outbreaks. Therefore, it is essential to identify new drug targets to treat this infection. Macrophage infectivity potentiator (Mip) proteins catalyse the folding of proline-containing proteins through their peptidyl pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 114 publications
0
7
0
Order By: Relevance
“…We focused on the macrophage infectivity potentiator (Mip) protein, a protein folding enzyme that exhibits peptidyl-prolyl isomerases (PPIase) activity, due to its established role in B. pseudomallei pathogenesis ( Norville et al, 2011b ). Additionally, Mip has been shown to be a virulence factor in other bacterial species including, Legionella pneumophila , Neisseria gonorrhoeae , Neisseria meningitidis and Coxiella burnetii , as well as parasites Trypanosoma cruzi and Leishmania major ( Cianciotto and Fields, 1992 ; Lundemose et al, 1993 ; Moro et al., 1995 ; Leuzzi et al., 2005 ; Reimer et al., 2016 ; Iwasaki et al., 2022 ; Debowski et al., 2023 ) Since it has been shown that other PPIase proteins have immunomodulatory roles during bacterial infections ( Pandey et al., 2017 ), we investigated, for the first time, the possible involvement of Mip in the innate immune response to B. pseudomallei infection. Using small molecule inhibitors designed to inhibit Mip, we demonstrated that treatment of B. pseudomallei -infected murine macrophages with the inhibitor AN_CH_37 resulted in a decrease in secreted pro-inflammatory cytokines IL-1β, TNFα and IL-6, and an increase in MCP-1, 24 hours post-infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We focused on the macrophage infectivity potentiator (Mip) protein, a protein folding enzyme that exhibits peptidyl-prolyl isomerases (PPIase) activity, due to its established role in B. pseudomallei pathogenesis ( Norville et al, 2011b ). Additionally, Mip has been shown to be a virulence factor in other bacterial species including, Legionella pneumophila , Neisseria gonorrhoeae , Neisseria meningitidis and Coxiella burnetii , as well as parasites Trypanosoma cruzi and Leishmania major ( Cianciotto and Fields, 1992 ; Lundemose et al, 1993 ; Moro et al., 1995 ; Leuzzi et al., 2005 ; Reimer et al., 2016 ; Iwasaki et al., 2022 ; Debowski et al., 2023 ) Since it has been shown that other PPIase proteins have immunomodulatory roles during bacterial infections ( Pandey et al., 2017 ), we investigated, for the first time, the possible involvement of Mip in the innate immune response to B. pseudomallei infection. Using small molecule inhibitors designed to inhibit Mip, we demonstrated that treatment of B. pseudomallei -infected murine macrophages with the inhibitor AN_CH_37 resulted in a decrease in secreted pro-inflammatory cytokines IL-1β, TNFα and IL-6, and an increase in MCP-1, 24 hours post-infection.…”
Section: Discussionmentioning
confidence: 99%
“…Three independent runs were performed for each protein and inhibitor/DMSO combination. The inhibition constant ( K i ) of SF235 and AN_CH_37 against Bps Mip were determined as previously described ( Iwasaki et al., 2022 ; Debowski et al., 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…Taken together, the results clearly show that the pyridinesubstituted compounds 2a-4a form N-oxides and then entirely The fact that the extent of metabolic conversion of N-oxides was much lower confirmed the hypothesis, that active metabolites, being the N-oxide, could be responsible for the long-lasting effect observed in vivo. [13] Evidence that the main metabolites of 2a, 3a, and 4a are the respective N-oxides was confirmed by comparison of the independently synthesized N-oxides [14] and the metabolites using HPLC-ultraviolet (UV) (method III) and LC/MS quadrupole time-offlight (qTOF) (method IV). With both methods, retention time and fragment spectra of both were in exact agreement (data are given in Supporting Information S1: Figure S3 and Figure S4).…”
Section: Metabolic Pathways and Structure Elucidation Of The Metabolitesmentioning
confidence: 97%
“…[9] Starting with a lead structure 1 (Figure 1), which exhibits anti-PPIase activity particularly for Legionella pneumophila, [10] Burkholderia pseudomallei, [11] Klebsiella pneumoniae, and Neisseria meningitidis, but also for the parasite Leishmania major, [12] a series of highly potent inhibitors were developed. Compounds that gained potency due to their additional side chain, in the linker between the two carbonyl moieties, were also shown to be efficient inhibitors of the Mip of Coxiella burnetii [13] and Neisseria gonorrhea. [14] All previously described Mip inhibitors (1, 2a, 3a, 4a, 2b, 3b, and 4b (Figure 1), which were used for this study, demonstrated strong binding affinity to Burkholderia pseudomallei-Mip (BpMip) in the fluorescence polarization assay (FPA), as well as high potency in the PPIase assay.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation